Spatio-temporal changes of water quality variables in a highly disturbed river - Z. Abdollahi; A. Kavian; S.H.R. Sadeghi (Global Journal of Environmental Science and Management)
Quality of river varies widely depending on the land use in the catchment and environmental factors. Many rivers in developing countries are unhealthy because they contain harmful physical, chemical and biological agents. Zanjanrud River, located in Zanjan Province, Iran, where recently faced human intervention needs a regular monitoring from upstream to downstream for sustainable management. Hence, the current study aimed to assess spatial and temporal variations of pollutant in Zanjanrud River in different stations from headstream to tail of the river. To achieve this goal, semi-monthly samples were collected from October 2015 to Jun 2016 at 5 stations along the river. The physicochemical variables were monitored and analysed using two-way analysis of variance. The results showed the highest values of suspended and dissolved solids and total solids (220.13±5.57, 641.6±39.63 and 793.6±34.5mg/L respectively) were at the tail site in low-flow period. Nitrate-nitrogen and nitrate were also highest (5.39±02.44 and 23.90±10.85 mg/L) at the middle of the river where was vicinity to farm lands. The values of pH and dissolved oxygen ranged from 6 to 8.15 and 0.5 to 4mg/L respectively with the highest values in high-flow period at most of the study sites. The maximum and minimum values of electrical conductivity (1439 and 256µs/cm) were recorded at tail site and headstream site respectively. Hardness had an increasing trend from upstream to downstream (189.60±53.53 to 515.83±64.77mg/L). Phosphorus was also lowest (0.09±0.04mg/L) at upstream. Results illustrated the high degree of pollutant in studied river. So, an effective management of erosion, domestic waste and agricultural activities in watershed is highly recommended.